Inflation and Budget Deficit: What is the Relationship in Portugal? - Rosa, Agostinho S. (2012)
The main causes of Portuguese inflation, based on annual data from 1954 to 1995, using the Johansen Method, allows us to conclude that variation in Portuguese inflation is determined essentially by foreign inflation and by variation in the effective exchange rate of the Portuguese Escudo (PTE). In the long-term, the relationship between inflation rate and the growth rate of unit labour costs is almost unitary. However, the response of inflation change to the equilibrium error between inflation rate and changes in unit labour costs is slow and almost insignificant, while the response of unit labour costs to this disequilibrium is fast and significant, what suggests that the direction of causality is much more evident from the inflation rate on unit labour costs, than the reverse. The budget deficit as a percentage of GDP, are not significant in the short-term, in relation to variation in inflation as a dependent variable. However, it is significant in the relation to unit labour costs as a dependent variable, so we can have an indirect positive relation between inflation and lagged budget deficit.